MANAJEMEN PENDIDIKAN MULTIKULTURAL PRESPEKTIF ULU AL-ALBAB - M. Fahim Tharaba (JURNAL AL-TANZIM, 2020)
This study aims to describe form and practice of multicultural education management based on Ulu al-Albab perspective at State Islamic University (UIN) of Maulana Malik Ibrahim Malang. This study uses a qualitative approach with a bibliographic resarch type with content analysis on the meaning of multicultural education management based on Ulu al-Albab perspective. This study figures out that (1) several aspects were developed as a form of multicultural education, including aspects of institutional development, facilities and infrastructure, academic, research and community service, student affairs, quality assurance, cooperation, building a spirit of giving and sacrifice, and development of academic character and noble morals; (2) multicultural education, closely related to university programs, including implementation of integration of Islam and science, optimizing the role of ma'had, increasing foreign language competence, increasing the quantity of human resources, revitalization of social and religious roles, implementation of information technology-based management, internationalization of universities and international cooperation towards World Class University (WCU), implementation of institutional development, and exploration of funding sources.